EVALUASI KINERJA SIMPANG TIGA TAK BERSINYAL DI JALAN RAYA LUMAJANG – PROBOLINGGO DESA KEBONAN KEC. KLAKAH KAB. LUMAJANG - Faisol Dwi Prasetyo; Rofi Budi Hamduwibawa; Taufan Abadi (Universitas Muhammadiyah Jember, 2019)
A road intersection is a point where various movements carried out by people with vehicles and without vehicles (pedestrians) meet which are not in the same direction. The intersection of the three being studied is on the Raya Probolinggo - Lumajang road near the Klakah gas station. This intersection is a three-way intersection that has a fairly large traffic flow and is passed by various types of motorized and non-motorized vehicles. fuel filling line. The purpose of this study is to reevaluate the performance of roads and intersections with no signal, to analyze the performance of roads and intersections for the next 5 years, and to analyze problem solving that occurs on these roads.